Inverter voltage dynamic compensation control optimization based on residual generators. (September 2022) - Du, Xuhao; Li, Bingyu; Zeng, Siming; Pang, Xianhai; Cheng, Linshu
Abstract: A dynamic compensated control strategy based on a residual observer combined with a gradient descent algorithm is proposed to address the power quality problem of inverters. A disturbance analysis of three-phase unbalance and harmonics is carried out based on the inverter. The robust control structure based on the residual observer is designed according to the theory of the Plug and Play control framework. Based on the need for fast response capability and stable performance of distributed grid systems, the gradient descent algorithm is optimized using the model matching principle, which provides a theoretical basis for the selection of initial points in the algorithm. Modelling simulations show that the obtained imbalance and THD are reduced by 50% compared to conventional control methods, thus verifying the effectiveness of the proposed control strategy.